Improvements in Blood Profiles of Canines Naturally Infected with Triple Blood Pathogens (Babesia vogeli, Ehrlichia canis, and Anaplasma platys) Subsequent to Doxycycline Monotherapy - Tuempong Wongtawan; Narin Sontigun; Kanpapat Boonchuay; Phatcharaporn Chiawwit; Oraphan Wongtawan; Orachun Hayakijkosol; Worakan Boonhoh (Animals, 2024)
), and most dogs displayed anemia and thrombocytopenia. These dogs were treated with doxycycline (10 mg/kg/day) orally for four weeks, and their blood profiles were monitored. Almost all pathogens were undetectable by PCR by day 14 and pathogens were all cleared by day 28. Most blood profiles significantly improved after 14 days. The improvement continued after 28 days. The red blood cell and platelet count (PLT) were increased in similar trends between mild-to-moderate and severe thrombocytopenia groups. The average PLT in the mild-to-moderate thrombocytopenia group raised to normal level by day 14, whereas in the severe group, it was gradually increased to normal level by day 70. We propose using doxycycline monotherapy for 28 days to eliminate all pathogens, and facilitate recovery and welfare in dogs suffering with triple blood pathogen infections.
Keywords: Vector-borne infectious diseases; Insect and Pesticide Research; Herpesvirus Infections and Treatments